Factography and Fiction: Mirroring in the Novel A Time of Death by Dobrica Ćosić - Božić, Snežana V.; Jovanović, Jelena V. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The subject of this paper is the analysis of Dobrica Ćosić’s novel A Time of Death I–IV (1972–1979), primarily from the perspective of possible worlds theory. One of the most important Serbian novels about the First World War, which critics have frequently defined as an epic novel, was inspiring for our research for at least two reasons: the first lies in the fact that historiographic metafiction is still the most prominent literary current in Serbian novelistic production, and the second is that contemporary readers have returned to Ćosić through intensive film adaptations in the recent years. The analysis and survey of the relationship between the factographic and fictional is precisely what led to the illumination and better understanding of the contemporary readers’ attitude towards the so-called neo-historical novel, which, according to Tihomir Brajović, began with Dobrica Ćosić. An interpretation of the characters in terms of possible worlds theory is at the center of attention, particularly the function of extratextual narrative identities of military leaders, statesmen, politicians, and warriors (Nikola Pašić, Aleksandar Karađorđević, Radomir Putnik, Stepa Stepanović, Živojin Mišić, Petar Bojović, Apis, and Stanislav Vinaver, among others). The specific aim of this paper is to understand the creative process whereby the characters were transformed and shaped as they made the transition from fact to fiction and, in this context, to analyze the documentary and artistic function of different types of texts that are incorporated into the narrative fabric of the novel. In particular, the author’s auto-poetic comments are deemed particularly relevant to unlocking the process of metamorphosis of the historical into the fictional. Two more questions are addressed as separate research challenges: (1) the importance of the specific way in which the author constructs the so-called historical characters to form national identity in the novel; and (2) the more general issue of historical truth, with particular regard to the nature of historiographic narrative. The methodological starting point for the interpretation of the characters is provided by the tenets of postclassical (cognitive) narratology, with priority given to Hilary Dannenberg’s typology of transworld identities.
Keywords: factography; fiction; historical novel; First World War; extratextual identities